PENERAPAN ALGORITMA SEQUENTIAL SEARCH DALAM PROSES PENCARIAN INFORMASI PADA SISTEM PEMBELAJARAN ORGAN JANTUNG MANUSIA - Wamiliana Wamiliana; Ade Hardiyanti; Wisnu Wardhana (Universitas Lampung, 2014)
Without no doubt, technology supports the human life and can be applied in many aspects, for example ineducation development. Learning process using computer as an aided tools are commonly used. The Applicationof Sequential Search Algorithm for The Searching Process of Information in The Learning System of Human’sHeart is an example of the application of computer in education that can be one of solution to help the learningprocess for teachers, lecturers, or students. In this research we use the sequential search algorithm searchingprocess in learning system of human’s heart which is one of the search methods to facilitate text searches of theinformation that required by the user. This system gives information about the material that is related to the heartorgan, i.e, heart anatomy, heart physiology, and heart pathology. The testing systems that used in this applicationis Black Box method. Black Box Testing is focuses on the functional requirements of the software. Black BoxTesting is used for testing the system in order to know if the system work well.Keyword: Black Box Testing; Heart; Sequential Search; Technology.